BISNIS JUAL BELI ONLINE (ONLINE SHOP) DALAM HUKUM ISLAM DAN HUKUM NEGARA - Tira Nur Fitria (ITB AAS INDONESIA Surakarta, 2017)
This study aims to find out about online shop (online business shop) in Islamic view (Islamic law). This research is qualitative descriptive. This study included literature to examine the written sources such as scientific journals, books referesni, literature, encyclopedias, scientific articles, scientific papers and other sources that are relevant and related to the object being studied. As for the object of study of this research is in the form of texts or writings that describe and explain about the business / online shop (online shopping), which become popular in Indonesia. Results from this study is Islam do business through online is allowed in accordance with Islamic Shari'a. While there are elements of usury, injustice, menopoli and fraud. Prophet hinted that buying and selling is lawful while consensual (Antaradhin), for sale or through an online business as having a positive impact because it is practical, fast, and easy for the buyer. If the business by via online not in accordance with the terms and conditions described above, online business is not allowed.